THE EXPERIENCE OF PARENTERAL METHOTREXATE TREATMENT IN A PATIENT WITH PAUCIARTICULAR JUVENILE RHEUMATOID ARTHRITIS - T. V. Sleptsova; E. I. Alexeeva; R. V. Denisova; T. M. Bzarova; K. B. Isaeva; E. V. Mitenko ("Paediatrician" Publishers LLC, 2012)
The article contains a history case of early onset of pauciarticular juvenile rheumatoid arthritis resistant to standard immunosuppressive treatment with methotrexate at a dose of 15 mg/m2 per week orally, with development of contractures and destructive changes in the joints. The resistance was successfully overcome with conversion to intravenous introduction at a dose of 25 mg/m2 per week. After 6 months of treatment acute inflammatory changes in the joins, arthralgia and morning joint stiffness were arrested, as well as laboratory markers of the active stage of disease lowered. After 12 months of treatment the motion capacity was completely restored in 3 of 4 affected joints. The non-active stage and remission were registered in 6 and 12 months, respectively. The remission has remained for 18 months.